Pengembangan Sumber Daya Manusia Di Organisasi Pendidikan - Hamsar Harahap (Proceedings of Annual Conference on Islamic Educational Management, 2021)
HR development is very necessary because it has important aspects for increasing HR productivity and also has certain goals which must be achieved for the progress and improvement of HR performance. HR development is basically done so that every organization's personnel become skilled people in carrying out their main tasks, through a fundamental understanding of the vision, mission, goals, targets and targets set by the organization and must be achieved with maximum and optimal results.